Effect of Effectiveness of the Board of Commissioners, Audit Committee, Quality of External Auditor on Tax Avoidance - Wirabrata, Esa Amelia (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
Supervision is one of the important components in realizing good corporate governance. Herein lies the importance of corporate governance, namely as a guarantor of the protection of the rights of shareholders. Corporate governance is one of the key elements in increasing economic efficiency, which includes a series of relationships between company management, the board of commissioners, shareholders and other stakeholders. This study aims to identify the effect of the effectiveness of the board of commissioners, audit committee, and the quality of external auditors on tax avoidance. The theory used in this study is the theory of agency theory, taxes, the board of commissioners, the audit committee, and external auditors. This study uses a sample of non-financial sector service companies during 2015-2019 using the purposive sampling method. The data used are obtained from financial reports and annual reports listed on the Indonesia Stock Exchange. Data analysis using multiple linear regression model, classical assumption test and hypothesis testing. The results of this study indicate that the effectiveness of the board of commissioners has no effect ontax avoidance, and the effectiveness of the audit committee does not affect tax avoidance, while the quality of external auditors affectstax avoidance.